2005
DOI: 10.1289/ehp.7640
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Adjustment in the Analysis of Environmental Contaminants and Human Health Risks

Abstract: The literature on exposure to lipophilic agents such as polychlorinated biphenyls (PCBs) is conflicting, posing challenges for the interpretation of potential human health risks. Laboratory variation in quantifying PCBs may account for some of the conflicting study results. For example, for quantification purposes, blood is often used as a proxy for adipose tissue, which makes it necessary to model serum lipids when assessing health risks of PCBs. Using a simulation study, we evaluated four statistical models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
254
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(257 citation statements)
references
References 31 publications
2
254
0
1
Order By: Relevance
“…Lipid adjustment of POP concentrations to some extent compensates for this, although lipid standardisation has also been reported to be prone to bias [20]. Inclusion of POPs unadjusted for lipids in the analyses did not, however, change our findings.…”
Section: Discussionmentioning
confidence: 61%
“…Lipid adjustment of POP concentrations to some extent compensates for this, although lipid standardisation has also been reported to be prone to bias [20]. Inclusion of POPs unadjusted for lipids in the analyses did not, however, change our findings.…”
Section: Discussionmentioning
confidence: 61%
“…At the time of delivery, mothers were mostly about 6-8 h without consumption of food. After fasting (meaning that there are no triglycerides of recent food consumption in the serum/ plasma), the concentration of OCs in serum/plasma lipids give a good reflection of the concentration in the fat tissue of the body (Schisterman et al, 2005). Indeed, we observed that the OC -present in plasma lipidsif expressed per wet weight (ng/mL), were positively associated with the plasma lipid concentration.…”
Section: Determinants Of Pollutant Levels In Cord Bloodmentioning
confidence: 74%
“…In the regression models, levels of OCs were expressed per mL serum, with plasma lipids included as a predictor (Schisterman et al, 2005). The partial R 2 indicates the % of variability explained by the covariate in the model.…”
Section: Discussionmentioning
confidence: 99%
“…The use of serum levels of lipophilic compounds standardized by serum lipids (by dividing serum concentration of the compound of interest by serum lipids) as an independent variable in epidemiologic models was recently shown to be highly prone to bias (Schisterman et al 2005). Thus, we regressed thyroid hormone concentrations on wet weight serum levels of PCBs, p,p′-DDE and HCB and adjusted for serum lipids as a covariate.…”
Section: Discussionmentioning
confidence: 99%